Studies on variability analysis in groundnut (Arachis hypogaea L.): Studies on variability analysis in groundnut (Arachis hypogaea L.) - R G GAWALI; A M MISAL; V G SONAWANE (Journal of Oilseeds Research, 2020)
The present investigation in groundnut was undertaken to study the extent of genetic variability for yieldcontributing characters in eighteen groundnut genotypes including three checks. These were evaluated at Oilseed Research Station, Latur during kharif 2016. The observations were recorded on selected five plants for seventeen characters. The estimates of genotypic and phenotypic coefficient of variation indicated that maximum GCV and PCV were observed for number of pods/plant, kernel yield/plant, pod yield/plant, harvest index, total sugar, thrips incidence, trichome frequency, SMCR. The estimates of variability were appreciably high for harvest index, number of pods/plant, kernel yield/plant and pod yield/plant, total sugar, and trichome frequency.